CLASSIFICATION OF COMPRESSION SPORTS JUHOSES WITH COMPRESSION CAPACITY - Shodiyev Ergashali Qudratshoyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on sportswear with a compressive effect on the body, their use, the purpose of use of compression sportswear, the range and functions of compression sportswear made of knitted fabrics.